Fairness Of Strategic Resource Allocation, Team Commitment And Commitment To Implementing Strategy In Indonesian International Joint Ventures - Lukman, Syukri; Nasurdin, Aizzat Mohd.; Mohamad, Osman (Universitas Islam Indonesia, 2012)

(untitled)
This study seeks to investigate the relationship between fairness of strategic resources allocation, management team’s commitment to multiple parties, and strategy of international joint ventures (IJVs) in Indonesia. Using a sample of 113 IJVs, the results of the regression analyses showed a positive relationship between fairness of strategic resources allocation and team’s commitment to implementing strategy whereby team commitment served as a mediator. In addition, fairness of strategic resources allocation was positively related to team commitment and team’s strategy. Im-plications, limitations, and suggestions for future research are discussed.